Reviving connections: Dene wellbeing and climate adaptation in Tthets'éhk'edélı̨ - Ireland, Margaret; Norwegian, Gladys; Hardisty, Marilyn; Latta, Alex; Gyapay, Julia; Sioui, Miguel; Pludwinski, Brandon; Sanguez, Arial; Falconer, Ashley; Bell, Mackenzie (Frontiers in Climate, 2026)
This article is a composite of nested stories about one Dene community's efforts to respond to change. It situates adaptation to climate change as the most recent in a longer history of social, economic, and cultural adjustments in response to the effects of colonization experienced by Tthets'éhk'edél ı̨ First Nation. As we delve into historical accounts of community collaboration in the money economy, the adoption of agricultural crops for food security, and a home-grown response to residential schools, self-determination and resilience emerge as consistent threads. These are both reinforced and put into question as we cross into a contemporary story about the community's responses to climate change across the past two decades, which is intertwined with the acceleration of social and economic change amidst the ongoing impacts of intergenerational trauma. The article concludes its overall story arc by describing the multi-year research partnership and writing collaboration for the article itself, which took shape even as flooding and fire threatened Tthets'éhk'edél ı̨'s existence. That final story is part methodological reflection and part deeper exploration of the community's struggles to revive Dene knowledge and ways of being by restoring connections with the land—even as the land is being rapidly transformed. Story as a mode of reconnection and reconnection as a form of climate adaptation put Indigenous understandings of health and wellness into focus as fundamental ingredients. Our reflections on the experiences of Tthets'éhk'edél ı̨ First Nation intersect with and contribute to the rising tide of voices and stories articulating Indigenous pathways toward alternate futures.